The Effects of Cassava on Lupine, Peanut and Velvet Bean Red Oncom Fermentation Using Neurospora sitophila - Cornelia, M.; Anggraini, B.; Darmawan, A.; Artanti, N.; Jayasena, Vijay; Kardono, L. (Science Alert, 2012)
Nowadays, the usage of Australian sweet lupine (Lupinus angustifolius) and velvet bean (Mucuna pruriens) are still limited to animal feed. In this research, the effect of legumes varieties (peanut, Australian sweet lupine and velvet bean) and cassava flour concentration (5, 20, 35%) on red oncom characteristics was studied. Legumes were soaked for 24 hand dehulled manually. Dehulled legumes mixed with cassava flour at different concentration. Then it was steamed, inoculated with Neurospora sitophila and fermented for 48 h. Legumes varieties affected on moisture, pH, hardness, mold growth and absorbance values of red red oncom. Concentration of cassava flour affected on moisture, pH, texture, firmness and absorbance values. Red on com had best characteristics when it is added by 20% cassava flour. Red oncoms made from peanut, Australian sweet lupine and velvet bean have no significant difference in protein content. Red oncoms made from Australian sweet lupine and velvet bean had good sensory characteristics.